Malingering assessment after severe traumatic brain injury in forensic psychology with a potential embedded symptom validity indicator of Symptom Checklist 90 - Liu, Cong; Lu, Qiuying; Rao, Guangxun; Chen, Xiaorui; Liang, Man; Liu, Zilong (Frontiers in Psychology, 2024)
Objective: Malingering of neuropsychological damage is common among traumatic brain injury patients pursuing disability compensation in forensic contexts. There is an urgent need to explore differences in neuropsychological assessment outcomes with different levels of cooperation. Method: 420 participants with severe traumatic brain injury were classified into malingering group, partial cooperation group and complete cooperation group according to Binomial Forced-Choice Digit Memory Test. Wechsler Adult Intelligence Scale, event-related potential component and symptom checklist 90 were applied subsequently to assess psychological status of participants. Results: Participants in malingering group presented lower scores in Binomial Forced-Choice Digit Memory Test, Wechsler Adult Intelligence Scale, lower P3 amplitude, and simultaneously higher scores in symptom checklist 90 than another two groups. The actual intelligence quotient of participants with malingering tendencies ranged mostly between normal and marginal damage, they often reported elevated whole scale score in symptom checklist 90. Cooperation Index (defined as the ratio of positive symptom distress index to global severity index, CI) was proposed and validated to function as an embedded validity indicator of symptom checklist 90, and the area under the receiver operating characteristic (ROC) curve was 0.938. When valued at 1.28, CI has the highest classification ability in differentiating malingering from non-malingering. Combined with the CI and P3 amplitude, the area under the ROC curve for malingering diagnosis further reached 0.952. Conclusion: Any nonoptimal effort in forensic context will lead to unexpected deviation in psychology evaluation results. CI is a potential candidate to act as an embedded validity indicator of symptom checklist 90. The combination of CI and P3 amplitude can help to identify malingering in participants after severe traumatic brain injury.